OBSERVACIONES PRELIMINARES SOBRE USO DE RECURSOS Y TEMPERATURA DE ACTIVIDAD EN ENSAMBLES DE HORMIGAS GRANÍVORAS DEL NORTE DE CHILE - Fuentes, José E.; Herrera, Sergio; Medel, Rodrigo G. (Acta Entomológica Chilena, 2022)
In arid zones the structure of assemblages of granivorous organisms is frequently influenced by competitiva interactions. In this study we analize some community attributes related to the use of seed baits by harvester and species from five Chilean localities along a precipitation gradient. In addition, we describe the daily activity of species. No more than three ant species were detected by locality, this result may be due to the low species richness of harvester ants in Chile. However, in three of the five studied localities, the overlap in seed bait utilization was less than expected by chance, being generally more frequent at temperature below 35°C. The low overlap in bait utilization might be adscribed, in principie, to the high territoriality of Solenopsis gayi.